Biophysical characterization of Dendrimer-Vismodegib complexes and skin penetration studies - Ybarra, David Emanuel; Calienni, María Natalia; Aguayo Frías, Eliana Taís; Lillo, Cristian R.; Alonso, Silvia del Valle; Montanari, Jorge; Alvira, Fernando Carlos (Sociedad Argentina de Biofísica, 2021)
Vismodegib (VDG) is an antineoplastic drug for basal cell carcinoma (BCC) treatment. Although it is effective it has severe side effects. The complexation of VDG with polyamidoamine dendrimers (PAMAM-D) could contribute to the reduction of its side effects by means of site-specific topical delivery and using lower amounts of drug. PAMAM-D are three-dimensional macromolecules with hydrophilic chemical groups on the surface and hydrophobic ones inner. The aim of this work is to design and optimize PAMAM-D complexes with VDG for the topical delivery of the active principle.We have used generation 4.0 and 4.5 PAMAM-D, with amino-ended (D.NH2), hydroxyl-ended (D.OH), and carboxyl-ended (D.COOH) groups. VDG was purified from commercial tablets. The complexes were obtained by incubation of VDG and PAMAM-D in methanol, and after drying under vacuum pellets were reconstituted in PBS. These complexes were characterized by spectroscopic techniques such as UV-Vis, fluorescence, among others, which provided a possible D-drug interaction mechanism.The VDG solubility in PBS reached after complexation was 67.3 µM with D.NH2, 54.0 µM with D.OH, and 63.0 µM with D.COOH. In the three complexes obtained it was corroborated that VDG interact with the inner hydrophobic pockets of PAMAM-D. Particularly, the electron clouds of VDG could interact electrostatically with the terminal amino groups of PAMAM-D. In contrast, VDG would not interact with the hydroxyl or carboxylic groups. On the other hand, the fluorescence characterization allowed us to select VDG complexes with D.NH2 and D.COOH to monitor skin penetration. Additionally, VDG accumulated in the skin was quantified by HPLC. The D.NH2:VDG penetrated deeper into human skin explants than D.COOH-VDG. The concentration of VDG recovered from the skin was 4.6 and 13.0 µM for D.NH2 and D.COOH, respectively.These results show a promising first approach to therapeutic potential use of these formulations in the treatment of BCC.This research has also been possible thanks to the economic contribution of Productos Roche S.A.Q. e I., Argentina, the National University of Quilmes and CONICET.
Keywords: Ciencias médicas y de la salud::Biotecnología médica::Biotecnología relacionada con la salud